2015
DOI: 10.1021/acs.energyfuels.5b00179
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Langmuir Equation of State for Asphaltene Adsorption at the Oil–Water Interface: Coal-Derived, Petroleum, and Synthetic Asphaltenes

Abstract: Preparation of synthetic asphaltenes: a) 1,2-bis(4-bromophenyl)-3,4,5,6-tetraphenylbenzene A mixture of tetraphenylcyclopentadienone (5.0 mmol), and bis(p-bromophenyl) acetylene (5.0 mmol) in diphenyl ether (20 ml) was heated to 260 °C overnight. Then the temperature was raised to 270 °C. After 69 h, the reaction mixture was cooled, and methanol (100 ml) was added. After stirring for 1 h, the product was filtered off, washed with methanol, and finally dried in vacuum overnight. Yield: Quantitative. b) 1,2-bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 61 publications
9
67
0
Order By: Relevance
“…In addition, the perpendicular orientation of PAC molecules observed here can be partly attributed to the oxygen functional groups, such as ketone and ester, present in the chemical structures. For PAC molecules without oxygen moieties, their polyaromatic core may prefer parallel to the interface, as reported by Banerjee and co-workers [15][16][17][18]. Indeed, it has been suggested by Mullins and co-workers 19,20 that the presence of oxygen moiety can alter the preferred orientations of PAC molecules from being parallel to being perpendicular.…”
mentioning
confidence: 74%
“…In addition, the perpendicular orientation of PAC molecules observed here can be partly attributed to the oxygen functional groups, such as ketone and ester, present in the chemical structures. For PAC molecules without oxygen moieties, their polyaromatic core may prefer parallel to the interface, as reported by Banerjee and co-workers [15][16][17][18]. Indeed, it has been suggested by Mullins and co-workers 19,20 that the presence of oxygen moiety can alter the preferred orientations of PAC molecules from being parallel to being perpendicular.…”
mentioning
confidence: 74%
“…In the last two decades, the interfacial viscoelasticity of asphaltenes have been studied, including air-water [15,[22][23][24][25][26][27][28][29][30][31] and oil-water interfaces with either air [32][33][34][35] or oil induced aggregation [14,[36][37][38][39][40][41][42][43] as well as oil-water interfaces with asphaltenes in the dispersed phase [43][44][45]. These studies have shown that the conditions by which the asphaltene film forms at the interface determine its rheological responses.…”
Section: Introductionmentioning
confidence: 99%
“…In the emulsions formation, the accumulation of asphaltenes at the water-oil interface forms a rigid film that directly influences the stability of the emulsion and prevents droplet coalescence of the dispersed phase [23,24]. According to Rane et al [25][26][27][28], asphaltenes form a film at the water-oil interface where asphaltene are adsorbed and form a stable multilayer that prevents separation of the immiscible phases. Because of their high polarity, asphaltenes can self-associate and be found at the water-oil interface as large aggregates, influencing the stabilization of the emulsions [29].…”
Section: Introductionmentioning
confidence: 99%